THE IMPACT OF INTRINSIC ELEMENTS ANALYSIS ON THE LION KING MOVIE (2019) FOR EFL LEARNERS - Anak Agung Putu Arsana; I Gusti Agung Putri Wirastuti; Ni Made Sarniasih; Ni Luh Putu Shintya Pradnyanita (Journal on Studies in English Language Teaching (JOSELT), 2023)
This study aims to analyse the impact of characterization and intrinsic elements on the lion king movie (2019) for EFL learners in the literary work of The Lion King movie. The movie genres of The Lion King are adventure, drama, and animation. This movie is a type of fable that talked about the struggle of a brave lion cub who was exiled to the middle of the forest and fights to reclaim his throne. Researchers obtained data from the appearance, characters, and dialogue in the movie The Lion King by using qualitative methods. Based on the results of this research, the researcher found five intrinsic elements namely theme, character, plot, setting, and point of view, and the researcher also got some positive impacts from the movie The Lion King for EFL learners.